Augmented Reality-Based Medicine Plants Learning Applications - M Julkarnain; Mohammad Taufan Asri Zaen; Nawassyarif Nawassyarif; Yudi Pratama; Yuliadi Yuliadi (The IJICS (International Journal of Informatics and Computer Science), 2021)
This study aims to design and build learning applications for medicinal plants based on Augmented reality so that they can be used as interactive learning media. The research methods used are qualitative and quantitative methods. Data collection methods used in this study are observation, interview, documentation, questionnaires and literature study and use the Prototype method as a software development method. This Augmented Reality-based medicinal plant learning application was built using the C# and Blender programming language to create 3-dimensional image designs. The result of developing this application is a learning media that can be run on a Smartphone by utilizing interactive Augmented Reality technology. When this application is opened, the main page will appear containing several menus, namely the play, guide, learning, and quite menus. The features contained in Augmented Reality-Based Medicinal Plant Learning, namely the 3D object scan feature, can find out information about plants with scanned images. This application can help people to get to know medicinal plants and their properties. And it can be an effective learning medium. Based on the results of the questionnaire, the application made by the author received a positive response from the respondents, in many category, such as the display, educational, satisfaction, interactive and music